Compositional analysis of pottery Huacramarca, Yanamayo southern basin, Ancash - Vega Centeno, Rafael (2014)
We report our results on compositional characterization of a ceramic sample from the site of Huacramarca, located in the Ancash region (Peruvian North-Central Highlands). ese results are based don XRD, XRF AND Mössbauer Espectroscopy analyses. Previous identication of compositional variability (based on macroscopical observations) suggest a pattern between dierent kinds of tempers and clay sources. Such patterns are strongly correlated with the variability identied through the outlined techniques, which allowed to go further and consider that alternative pottery-making processes were responsible for the Huacramarca assemblage. is suggests the possibility of dierent groups of people co-habiting in the settlement during the early part of the Late Intermediate Period.